Aberrant functional network connectivity in psychopathy from a large (N = 985) forensic sample. Issue 6 (2nd March 2018) - Espinoza, Flor A.; Vergara, Victor M.; Reyes, Daisy; Anderson, Nathaniel E.; Harenski, Carla L.; Decety, Jean; Rachakonda, Srinivas; Damaraju, Eswar; Rashid, Barnaly; Miller, Robyn L.; Koenigs, Michael; Kosson, David S.; et al.
Abstract: Psychopathy is a personality disorder characterized by antisocial behavior, lack of remorse and empathy, and impaired decision making. The disproportionate amount of crime committed by psychopaths has severe emotional and economic impacts on society. Here we examine the neural correlates associated with psychopathy to improve early assessment and perhaps inform treatments for this condition. Previous resting‐state functional magnetic resonance imaging (fMRI) studies in psychopathy have primarily focused on regions of interest. This study examines whole‐brain functional connectivity and its association to psychopathic traits. Psychopathy was hypothesized to be characterized by aberrant functional network connectivity (FNC) in several limbic/paralimbic networks. Group‐independent component and regression analyses were applied to a data set of resting‐state fMRI from 985 incarcerated adult males. We identified resting‐state networks (RSNs), estimated FNC between RSNs, and tested their association to psychopathy factors and total summary scores (Factor 1, interpersonal/affective; Factor 2, lifestyle/antisocial). Factor 1 scores showed both increased and reduced functional connectivity between RSNs from seven brain domains (sensorimotor, cerebellar, visual, salience, default mode, executive control, and attentional). Consistent with hypotheses, RSNs from the paralimbic system—insula, anterior and posterior cingulate cortex, amygdala, orbital frontal cortex, and superior temporal gyrus—were related to Factor 1 scores. No significant FNC associations were found with Factor 2 and total PCL‐R scores. In summary, results suggest that the affective and interpersonal symptoms of psychopathy (Factor 1) are associated with aberrant connectivity in multiple brain networks, including paralimbic regions.